The Influence of Health Education on Knowledge of Breastfeeding Mothers about the Benefits of Katuk leaves Againts Improvement Breast Milk Production - Ita Noviasari (STIKes Patria Husada Blitar, 2023)
Katuk leaves play a role in the prolactin reflex and stimulate the alveoli to produce breast milk, because they contain polyphenyls and steroids. It also stimulates the hormone oxytocin so that it stimulates the release of breast milk. Katuk leaves also contain several aliphatic compounds. Katuk leaves which can increase milk production, are thought to originate from the hormonal effects of sterol chemical compounds that are estrogenic. Type of research One Group Pretest Posttest Design with pre-test and post-test design. The sample used was mothers who were breastfeeding with babies less than 2 months old, a total of 30 respondents were taken by total sampling. The research instrument used questionnaires and leaflets. The statistical test uses the Shapiro Wilk test with the SPSS 16.0 program. 50% of respondents had sufficient knowledge and 93.3% of respondents had good knowledge regarding the benefits of katuk leaves in increasing milk production. Based on Shapiro Wilk's statistical test, it was found that p value = 0.000, so that p value = 0.000 < Î± = 0.05. The influence of health education on health education about the benefits of katuk leaves to increase milk production in nursing mothers. Conclusion: There is an effect of health education on mother's knowledge about the benefits of katuk leaves to increase milk production